2016
DOI: 10.1186/s13023-016-0430-2
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 gene polymorphisms are associated with serum KL-6 levels and pulmonary dysfunction in pulmonary alveolar proteinosis

Abstract: BackgroundKL-6, a human MUC1 mucin, is a sensitive biomarker for interstitial lung diseases including pulmonary alveolar proteinosis (PAP). A correlation between MUC1 gene single nucleotide polymorphism (SNP) rs4072037 genotype and serum KL-6 levels has been reported. This study was aimed at investigating the correlation between MUC1 SNP genotype, severity of disease and disease outcome in PAP.MethodsTwenty four patients with PAP and 30 healthy volunteers were studied. MUC1 rs4072037 was detected by using a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…The reason of this discrepancy might be involved in MUC1 gene polymorphisms which are associated with serum KL-6 levels (19). The association between bile KL-6 and MUC1 gene polymorphisms was uncertain, more study is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The reason of this discrepancy might be involved in MUC1 gene polymorphisms which are associated with serum KL-6 levels (19). The association between bile KL-6 and MUC1 gene polymorphisms was uncertain, more study is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were obtained by venipuncture and stored at -80˚C until measurement. Plasma KL-6 levels were measured by a Nanopia KL-6 assay (SEKISUI MEDICAL, Tokyo) using a latex-enhanced immunoturbidimetric assay method as used in previous studies [30,31]. Previous study conducted in our institution reported that within-laboratory precisions of Nanopia KL-6 assay were < 2% of coefficient of variation [32].…”
Section: Measurement Of Kl-6mentioning
confidence: 99%
“…Interstitial lung disease (ILD) is a group of diseases characterized by various forms of pulmonary interstitial inflammation and fibrosis, which are usually chronic, progressive, and fatal, causing death 2‐5 years after diagnosis in most patients . These disorders primarily affect the pulmonary interstitium, alveolar cavity, and bronchioles .…”
Section: Introductionmentioning
confidence: 99%
“…Interstitial lung disease (ILD) is a group of diseases characterized by various forms of pulmonary interstitial inflammation and fibrosis, which are usually chronic, progressive, and fatal, 1 causing death 2-5 years after diagnosis in most patients. 2,3 These disorders primarily affect the pulmonary interstitium, alveolar cavity, and bronchioles. 4 Presently, clinical diagnostic methods of ILD are extremely limited, including HRCT, pulmonary function test, bronchial lavage, lung biopsy, and other examinations, which require specific medical equipment and will lead to patient discomfort.…”
Section: Introductionmentioning
confidence: 99%